The coinage of Agathokles of Syracuse: Sicilian and Hellenistic influences - de Lisle, C (Royal Numismatic Society, 2017)
Agathokles of Syracuse stands at the intersection of Sicilian tyranny and Hellenistic monarchy. The only contemporary evidence for how he related to these two styles of rule is his coinage. Where many scholars have seen this coinage as evidence for a transition from one style of rule to the other, I argue that it demonstrates his continuous engagement with and adaptation of Macedonian styles of representation from the very beginning of his rule, but also the enduring significance of the local Sicilian context to Agathokles’ decision-making and self-representation.